Stabilization of Nonlinear Systems Using Receding-horizon Control Schemes A Parametrized Approach for Fast Systems - Alamir, Mazen; SpringerLink (Online service) (London : Springer London, 2006)
While conceptually elegant, the generic formulations of nonlinear model predictive control are not ready to use for the stabilization of fast systems. Dr. Alamir presents a successful approach to this problem based on a co-operation between structural considerations and on-line optimization. The balance between structural and optimization aspects of the method is dependent on the system being considered so the many examples aim to transmit a mode of thought rather than a ready-to-use recipe; they include: - double inverted pendulum; - non-holonomic systems in chained form; - snake board; - missile in intercept mission; - polymerization reactor; - walking robot; - under-actuated satellite in failure mode. In addition, the basic stability results under receding horizon control schemes are revisited using a sampled-time, low-dimensional control parameterization that is mandatory for fast computation and some novel formulations are proposed which offer promising directions for future research.
Generic Framework -- Definitions and Notation -- The Receding-Horizon State Feedback -- Stabilizing Schemes with Final Equality Constraint on the State -- Stabilizing Formulations with Free Prediction Horizon and No Final Constraint on the State -- General Stabilizing Formulations for Trivial Parametrization -- Limit Cycles Stabilizing Receding-Horizon Formulation for a Class of Hybrid Nonlinear Systems -- Generic Design of Dynamic State Feedback Using Receding-Horizon Schemes -- Application Examples -- Swing-Up Mechanical Systems -- Minimum-Time Constrained Stabilization of Nonholonomic Systems -- Stabilization of a Rigid Satellite in Failure Mode -- Receding-Horizon Solution to the Minimum-Interception-Time Problem -- Constrained Stabilization of a PVTOL Aircraft -- Limit Cycle Stabilizing Receding-Horizon Controller for the Planar Biped Rabbit.
Keywords: Engineering; Chemical engineering; System theory; Calculus of variations; Automotive engineering; Control engineering; Robotics; Mechatronics; Engineering; Control; Control, Robotics, Mechatronics; Systems Theory, Control; Calculus of Variations and Optimal Control; Optimization; Automotive Engineering; Industrial Chemistry/Chemical Engineering; Electronic books